CLINICAL-IMMUNOLOGICAL EFFECTIVENESS OF RIBOMUNYL IN CHILDREN WITH VIRUS-INDUCED BRONCHIAL ASTHMA - E. B. Belan; E. M. Nikiforova; T. E. Zayachnikova; l. N. Shishimorov; O. V. Magnitskaya (Фармация и фармакология (Пятигорск), 2020)
The aim of the study is to research the effects of immunostimulant Ribomunyl in virus-induced bronchial asthma (VBA) children.Materials and methods. 14 virus-induced bronchial asthma (VBA) children were agministrated with immunostimulant Ribomunyl as a part of complex therapy in a 18-month trial (3 cycles of treatment). The comparison group consisted of 16 patients who received only standard therapy for bronchial asthma. At the end of the study, against the background of basic BA therapy, the following parameters were estimated: the frequency of acute respiratory viral infections (ARVI), the need for antibacterial therapy, the frequency of IgG to respiratory-syncytial virus (RSV) prevalence, the serum level dynamics of total IgE, IFN-γ, interleukin-4 (IL-4), interferon gamma (IFN-γ).Results. The inclusion of Ribomunyl into the basic therapy complex in virus-induced bronchial asthma (VBA) children, made it possible to reduce the need for the VBA basic therapy complex by 50% and by 12,5% (р=0,0279). At the same time, as for the frequency of acute respiratory viral infections (ARVI), there was a comparable decrease in both groups, but in the main group the number of cases requiring antibiotic therapy decreased from 78.6% to 42.9% (p=0.0199). The inclusion of Ribomunyl into the basic therapy complex resulted in the decrease of the total IgE serum level; in the patients with the initial presence of IgG to the respiratory syncytial virus (RSV), the IL-4 level decreased and the IFN-γ level increased.Conclusion. Ribomunyl improves the treatment of virus-induced bronchial asthma (VBA) children, herewith the dynamics of immunological indicators is more in RSV-seropositive patients.